SCHOOL CULTURE AND THE NORMALIZATION OF TOXIC PRODUCTIVITY: A REVIEW OF THE SOCIOLOGICAL LITERATURE ON PERFORMANCE PRESSURE AMONG STUDENTS: BUDAYA SEKOLAH DAN NORMALISASI TOXIC PRODUCTIVITY: KAJIAN LITERATUR SOSIOLOGIS ATAS TEKANAN KINERJA DI KALANGAN PELAJAR - Oman Sukmana; Amin Saleh; Fahmi Rahmat Kangiden; Moh. Syahrudin Mokoagow (SOSIOEDUKASI, 2025)
The phenomenon of increasing academic pressure in schools has normalized toxic productivity as the ideal identity of students. A culture of meritocracy and excessive competition forces students to constantly pursue productivity without considering mental well-being. This study aims to analyze sociologically how school culture shapes and legitimizes performative pressures that negatively impact students' emotional health. The method used is a systematic literature review with a qualitative approach based on the perspective of educational sociology and critical sociology. Data sources were obtained from relevant journal articles, academic books, research reports, and conference proceedings, especially publications of th years, through searches on Google Scholar, Scopus, Web of Science, and DOAJ. The analysis process is carried out thematically and narratively to identify conceptual patterns, using the theoretical framework of Pierre Bourdieu and Michel Foucault. The results show that the ranking system, high expectations, and emphasis on academic achievement create a competitive atmosphere that triggers chronic stress, anxiety, and identity crises among students. The role of teachers and schools as agents of normalization reinforces this cycle, often unconsciously. In conclusion, a more balanced transformation of the educational paradigm is needed by emphasizing mindful learning, psychosocial support, and policies that prioritize students' mental health holistically. e last ten